Content analysis of breast milk substitutes marketing on Chinese e‐commerce platforms. Issue 2 (25th February 2022) - Han, Shannon; Chen, Huixi; Wu, Yanting; Pérez‐Escamilla, Rafael
Abstract: China has the largest and fastest‐growing breast milk substitutes (BMSs) market and a disproportionately low exclusive breastfeeding rate. Many BMS manufacturers have established Chinese e‐commerce stores. This marketing is of concern as it is likely to undermine breastfeeding. This study aimed to identify: (1) the marketing themes and strategies used to promote BMSs on the Chinese BMSs e‐commerce websites; (2) if and how digital BMSs marketing may deviate from the World Health Organization Code of Marketing of Breast Milk Substitutes (the Code) recommendations. Content analysis was conducted on the flagship websites of 10 BMSs companies on the Chinese e‐commerce platform "TMall" in July 2019. The main landing page ( n  = 10) of the flagship TMall website and the product description page ( n  = 113) of all individual formulas (Stages 1–3) within each company's TMall website were examined. The content was analysed and coded using an iterative thematic analysis approach. Emphasis on Premiumization and Science & Nutrition was the most commonly used marketing approaches. A total of 27.4% of the product description pages sampled used images of infants (<12 months), 33.6% made favourable comparisons of BMSs to breast milk, and only 34.5% included probreastfeeding statements. Marketing strategies were often inconsistent with the Code, and companies used "creative" ways to target mothers, often circumventing the Code recommendations. Unsubstantiated information was commonplace and of concern, because the e‐commerce platform provided easy opportunities for bulk purchases. National regulatory actions are urgently needed to monitor online BMS marketing and the undermining of breastfeeding in China. Abstract : Breast milk substitutes (BMSs) marketing strategies in e‐commerce platforms in China were often inconsistent with the World Health Organization Code, and companies used "creative" ways to target mothers. National regulatory actions are urgently needed to monitor online BMS marketing and the undermining of breastfeeding in China. Key messages: China is the largest market for breast milk substitutes (BMSs) and has a disproportionately low exclusive breastfeeding rate. E‐commerce platforms are becoming a popular channel of BMSs marketing and bulk purchases. Marketing BMS messages focus heavily on claims for improved child health and development outcomes that are oftentimes not backed up by scientific evidence. There is an urgent need for national actions to monitor online BMSs marketing and reestablish regulatory policies that enforce the World Health Organization Code for Marketing of BMSs in China.